Aptian angiosperm pollen from the Ticó Flora Patagonia, Argentina - Archangelsky, Sergio (2013)
Six angiosperm pollen types studied with SEM are recorded in the Cretaceous (early Aptian) Tico´ flora on the basis of material recovered from two localities: Anfiteatro de Tico´ and Bajo Tigre. Clavatipollenites dominates, with four types described. The other two types, based on single specimens, were referred to Retimonocolpites and to the Anacostia type. Comparisons are made with similar species found in other Cretaceous paleofloristic regions and with other Aptian pollen assemblages from Patagonia. The chloranthaceous affinity of Clavatipollenites agrees with known paleobotanical, sedimentological, and paleoclimatical data obtained for the same fossiliferous horizons of the Anfiteatro de Tico´ Formation studied here. During the early Aptian, a warm and humid paleoclimatic belt extended to latitudes greater than 60S in SW Gondwana. This belt is known to have persisted until the late Aptian in southern Patagonia. The angiosperm pollen variety is further underscored by fossil leaves found in two of the horizons studied here, suggesting that angiosperms may have existed during the Barremian in SW Gondwana (Patagonian Province).